Market Climate and Customer Preferences Towards Franchisor of Islamic Kindergarten in Shah Alam - Nur El Ikhsan (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
This study aims to identify market climate and customer preferences of people around Shah Alam, Malaysia towards franchisor of Islamic kindergarten. The research method used is quantitative approach and questionnaires are distributed to 40 parents around Shah Alam who have children and putting their children to have pre-education among 3 Islamic kindergarten brand. The result of this study explained that most consumers engage their children to pre institutions the school grounds to increase the ability and social interaction. The main consideration consumers in choosing pre -school education are the type of program services offered and teacher skills and knowledge. While biggest decision maker was the husband. Price sensitivity is low with costs incurred for pre-school activities people feel suitable is more than RM 200 per month. Lastly, if consumers are not satisfied then the action taken is complain directly to the pre-school and directly stop using the service.